Usefulness of Stereotactic Radiotherapy Using CyberKnife for Recurrent Lymph Node Metastasis of Differentiated Thyroid Cancer - Joji Kawabe; Shigeaki Higashiyama; Mitsuharu Sougawa; Atsushi Yoshida; Kohei Kotani; Susumu Shiomi (Case Reports in Endocrinology)
A woman in her 60s presented with a recurrent lymph node metastasis from a papillary thyroid carcinoma in the right parapharyngeal space. She had already undergone total thyroidectomy, five resections for cervical lymph node metastases, and right carotid rebuilding. Surgical resection of the current metastasis was impossible. 131I-radioiodine therapy (RIT) with 3.7 GBq 131I was not effective; therefore, stereotactic radiation therapy (SRT) using a CyberKnife radiotherapy system was scheduled. The prescription dose was 21 Gy, and a dose covering 95% of the planning target volume (PTV) in three fractions was administered. The PTV was 4,790 mm3. Follow-up magnetic resonance imaging conducted 3 and 12 months after the SRT demonstrated a remarkable and gradual reduction of the recurrent lymph node metastasis in the right parapharyngeal space and no evidence of recurrence. For multidisciplinary therapy of unresectable and/or RIT unresponsive locoregional lymph node metastases and recurrences of DTC, SRT using the CyberKnife system should be considered.